Survival Outcomes for Patients With Indeterminate 18FDG-PET Scan for Extrahepatic Disease Before Liver Resection for Metastatic Colorectal Cancer: A Retrospective Cohort Study Using a Prospectively Maintained Database to Analyze Survival Outcomes for Patients With Indeterminate Extrahepatic Disease on 18FDG-PET Scan Before Liver Resection for Metastatic Colorectal Cancer. Issue 5 (May 2018) - Wong, Geoffrey Yuet Mun; Kumar, Rajiv; Beeke, Carol; Ullah, Shahid; Chen, John; Karapetis, Christos; Price, Timothy; Padbury, Rob
Abstract : Objective: The aim of this study was to evaluate overall survival (OS) and cancer recurrence for patients with indeterminate positron emission tomography (PET) scan for extrahepatic disease (EHD) before liver resection (LR) for colorectal liver metastases (CLMs). Summary of Background Data: Indeterminate EHD as determined by PET imaging indicates a probability of extrahepatic malignancy and potentially excludes patients from undergoing LR for CLM. Methods: In a retrospective analysis of prospectively collected data from February 2006 to December 2014, OS for patients with indeterminate EHD on 18 FDG-PET scan before LR for CLM was performed using standard survival analysis methods, including Kaplan-Meier estimator and Cox proportional hazard models for multivariate analyses. Postoperative imaging was used as reference to evaluate the association between indeterminate EHD and recurrence. Results: Of 267 patients with PET scans before LR, 197 patients had no EHD and 70 patients had indeterminate EHD. Median follow-up was 33 months. The estimated 5-year OS was 60.8% versus 59.4% for indeterminate and absent EHD, respectively ( P = 0.625). Disease-free survival was comparable between both groups ( P = 0.975) and overall recurrence was 57.1% and 59.5% for indeterminate and absent EHD, respectively ( P = 0.742). About 16.9% of recurrence was associated with the site of indeterminate EHD, with 80% of associated recurrence occurring in the thorax. Conclusions: The site of indeterminate EHD appears to have a predictive value for recurrence, with indeterminate EHD in the thorax having a higher probability of malignancy. The evidence in this report supports the critical evaluation of PET scan results and that patients are not denied potential curative LR unless the evidence for unresectable EHD is certain.